CREATION OF ADDED VALUE FROM THE POSITION OF SUSTAINABLE DEVELOPMENT OF THE COMPANY - Наталія Краснокутська; Гао Лян (Економіка та суспільство, 2022)
The aim of the article is to study the structure of added value, taking into account the nature of the implementation of socially oriented projects in the practice of activity. To do this, the dynamics and structure of value added are studied, its level and structure are compared for enterprises that adhere to a strategic and reactive approach to the implementation of economic, social and environmental goals of sustainable development. The study is based on the data of 15 enterprises operating in the food production segment. The research period is 2018-2020. According to the results of the study, it was concluded that the absolute value of added value and its share in the composition of income for the period under consideration increased. It is noted that the largest share in the value added of the sample enterprises is labor costs. It is argued that for enterprises that adhere to the model of reactive corporate social responsibility, the share of profit in the value added is high; for enterprises with strategic corporate social responsibility – the share of staff costs.